Between Democratic Security and Democratic Legality. Constitutional Politics and Presidential Re-election in Colombia (2014)
This paper presents an analysis of the political and legal debate of the declaration of unconstitutionality of the referendum that sought the re-election presidential second term in 2010. On the other hand, it exposes the debate between those who spoke of bias and political argument in the court ruling related to the idea of “democratic security”; while others speak of the persistence of “democratic legality” consisting of autonomy guaranteed legal reasoning from deliberative processes. Finally, it is noted that the degree of institutionalization of discourse of the Court is an important factor that speaks in favor of it’s independence.